Factors Influencing Public Interest in Using Sharia Financial Products: (Case Study of Ngroto Village, Gubug District, Grobogan Regency) - Jihad Nurfebrianda; Nurani Puspa Ningrum; Tuti’ Nadhifah (Indonesian Economic Review, 2026)
Research This aim For analyze factors that influence interest public in use product finance Sharia in the Village Ngroto, District Hut, Regency Grobogan. Development industry finance Sharia in Indonesia shows significant growth​ And contribute to inclusion finance, but participation public rural Still relatively low. Research This test influence religiosity, beliefs, and literacy finance sharia to interest community. The method used is approach quantitative with cross -sectional design on 70 selected respondents purposively. Data collected through questionnaire Likert scale and analyzed use multiple linear regression with level significance 0.05. Results​ study show that religiosity and literacy finance sharia influential positive significant to interest society, whereas trust influential negative significant. In terms of simultaneous, third variables influential significant with mark coefficient determination (R²) of 0.713, which means 71.3 % of the variation interest can explained by the research model. Findings This confirm that mark religious and understanding finance sharia own role dominant in increase participation public rural areas. Research This give contribution theoretical in study economy behavior sharia as well as implications practical for institution finance sharia in strengthening literacy programs and strategy promotion based community.